2017
DOI: 10.1186/s40425-017-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Intratumorally injected pro-inflammatory allogeneic dendritic cells as immune enhancers: a first-in-human study in unfavourable risk patients with metastatic renal cell carcinoma

Abstract: BackgroundAccumulating pre-clinical data indicate that the efficient induction of antigen-specific cytotoxic CD8+ T cells characterizing viral infections is caused by cross-priming where initially infected DCs produce an unique set of inflammatory factors that recruit and activate non-infected bystander DCs. Our DC-based immunotherapy concept is guided by such bystander view and accordingly, we have developed a cellular adjuvant consisting of pre-activated allogeneic DCs producing high levels of DC-recruiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“… 37 Our research findings are also pertinent to the clinical setting, as the alloDCs approach using i.t. injected mature pro-inflammatory alloDCs has already been successfully tested in a phase I/II clinical trial in patients with mRCC 21 and is ongoing in a randomized multicenter phase II study in metastatic RCC patients (NCT02432846).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 Our research findings are also pertinent to the clinical setting, as the alloDCs approach using i.t. injected mature pro-inflammatory alloDCs has already been successfully tested in a phase I/II clinical trial in patients with mRCC 21 and is ongoing in a randomized multicenter phase II study in metastatic RCC patients (NCT02432846).…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral administration of pro-inflammatory alloDCs (Ilixadencel) was recently shown to induce an anti-tumor immune response that may prolong survival in unfavorable risk metastatic renal cell carcinoma (mRCC)-patients given subsequent standard of care. 21 Additionally, we have shown that pro-inflammatory, adenoviral-transduced alloDCs created an immunostimulatory environment in vitro , which promoted the maturation of bystander DCs able to cross-present antigens to antigen-specific effector T cells (co-published data). Here, we evaluate alloDCs in combination with an infection-enhanced adenoviral vector in order to load alloDCs with TAAs.…”
Section: Introductionmentioning
confidence: 89%
“…Clinical studies combining DC vaccination with chemotherapy, radiotherapy, and/or targeted therapy have been performed. Without extensive elaboration on these studies, the safety of combining DC vaccination with these modalities is confirmed in phase I trials ( 97 100 ). Futhermore, ample data exist suggesting efficacy ( 101 , 102 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, resting mast cells and dendritic cells showed the protective factors in ccRCC, and the dendritic cells was reported as an immune enhancer utilized as baseline in immunotherapy for solid tumors (34,35). What is more, we also used another method to infer the fractions of immune cells based on the characteristic immune cells marker gene (36).…”
Section: Discussionmentioning
confidence: 99%